Structure and Electrical Study of New Chemically Modified Poly(vinyl chloride) - F. Ammari; M. Dardouri; M. Kahlaoui; F. Meganem (International Journal of Polymer Science)
The aim of this work was to study the structural and electrical properties of a new polymer obtained by functionalization of a commercial poly(vinyl chloride) (PVC) (Mw = 48000) by grafting aminoalkyl and aminoaryl groups. Modified poly(vinyl chloride) was prepared in two steps. The structural properties of the polymer were systematically investigated by varieties of techniques as differential scanning calorimetric (DSC), thermogravimetry analysis (TG), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. The electrical properties of the polymer were studied by electrochemical impedance spectroscopy (EIS).